Optimal control strategy for large-scale VRB energy storage auxiliary power system in peak shaving. (September 2020) - Li, Junhui; Hu, Dacheng; Mu, Gang; Wang, Shuai; Zhang, Zheshen; Zhang, Xiaochi; Lv, Xiangyu; Li, Dexin; Wang, Jiarui
Highlights: Relationship between charging/discharging power and efficiency of the ES is fitted. Mathematical model for the efficiency of large-scale VRB ES was established. Control strategy is designed for ES units to optimize overall ES efficiency. The effect of the control strategy applied to the peak-shaving scenario is obvious. Abstract: Large-scale battery energy storage is an inevitable trend in energy storage development. The large-scale all-vanadium liquid-flow battery energy storage system contains a large number of battery energy storage units. Current operation methods usually study large-scale energy storage as an equivalent model. There is a lack of optimization for the operation of modular energy storage units. Efficient and stable operation of large-scale energy storage needs to coordinate the operation of various energy storage units. A battery simulation model was built according to the working mechanism and external characteristics of the vanadium redox battery (VRB). Based on the simulation model, the voltage and current loss characteristics of the vanadium redox battery under the rated power charging and discharging mode were studied. Based on the model, the change in charging and discharging efficiency under different powers is measured. The power–efficiency coupling relationship is studied. The power–efficiency coupling relationship provides the basis for power allocation with the aim of optimizing efficiency. Then, combining the structure of the large-scale vanadium redox battery energy storage system and the power–efficiency coupling relationship, a large-scale energy storage system efficiency mathematical model is constructed. In a peak shaving scenario, aiming at optimizing the efficiency of the energy storage system and according to the efficiency mathematical model of the large-scale energy storage system, a coordinated and optimized operation strategy of the energy storage module is proposed. This module improves the efficiency of the energy storage system.